Analisis Perbandingan Sistem Kerja Earth Leakage Circuit Breaker (ELCB) dan Miniature Circuit Breaker (MCB) Sebagai Sistem Proteksi Tegangan Sentuh Tidak Langsung - Azhari, Fajar; Lesmana, Dicky; Lubis, Zulkarnain (Politeknik Harapan Bersama Tegal, 2024)
Human safety against touch voltage hazards is the most important factor in electrical power systems. Touch voltage hazards can occur if a person directly or indirectly touches live electrical parts. Indirect contact can happen when a person touches exposed conductive parts of equipment that are normally not energized but can become energized due to leakage current caused by insulation failure in electrical cables. Therefore, protection against indirect touch voltage is necessary. This study aims to analyze the protection against indirect contact voltage using an Earth Leakage Circuit Breaker (ELCB) and a Miniature Circuit Breaker (MCB). In this study, a 30 mA ELCB and a 2 A MCB were used as protection against indirect touch voltage hazards. The research data were obtained using the experimental method by conducting laboratory experiments. The laboratory experiment results showed that the 30 mA ELCB is more sensitive as protection against indirect touch voltage compared to the MCB. This is because the working principle of the ELCB is based on the leakage current occurring at the exposed conductive parts, whereas the working principle of the MCB is based on the total current (leakage current and load current) flowing through the MCB.